Proposta de aceleração da oferta de vagas em creches na cidade de São Paulo - Reis, Sérgio Roberto Guedes (2011)
The main purpose of this dissertation is to propose the acceleration of the supply of places in public day care centers in the city of São Paulo. Developed from a Term of Reference organized by the Municipal Education Secretariat of São Paulo (SME), this paper has as its object the study of the public policy of day care in this city, which serves about 190,000 children, but faces a significant deficit of approximately 127 000 places in the face of a universe of about 736 000 children between 0 and 3 years. In the light of theoretical and empirical field of management and public policy, we attempted to contextualize the problem and to indicate alternatives to expand the coverage of the afforementioned service. Initially, we attempted to traverse the historical background and legal framework regarding the provision of the early childhood care and education policy. Based on expert interviews and on secondary data collection, we examined the current design and implementation of the daycare schemes. With this diagnosis, we have identified, among other, the following challenges to be overcomed: (i) the acceleration of the expansion of the number of places in day care centers, (ii) the need of equalizing the distribution of that expansion according to socioeconomic vulnerability criteria, (iii) the urge to improve the quality care entities and to reduce the inequality of standards of quality between the public and and the privatecovenant sectors, (iv) the improvement of the management capacity and planning of EMS, and (v) the establishment of an integrated vision of early childhood policy for the municipality of São Paulo. The proposal suggests, therefore, investments, actions and efforts in order to increase the SME's management capacity to deal with those obstacles and demands - including the potential for collaboration with other organizations and actors -, as long as changes in the current design of the daycare policy, the use of policy planning, monitoring and evaluation tools. A simulation of the implementation of a strategic planning to day-care policy was developed, for illustrative purposes; it covers two sets of alternative procedures for the expansion of places and their associated budget requirements.